2010
DOI: 10.1051/0004-6361/201014798
|View full text |Cite
|
Sign up to set email alerts
|

The influence of albedo on the size of hard X-ray flare sources

Abstract: Context. Hard X-rays from solar flares are an important diagnostic of particle acceleration and transport in the solar atmosphere. However, any observed X-ray flux from on-disc sources is composed of direct emission plus Compton backscattered photons (albedo). This affects both the observed spectra and images and the physical quantities derived from them, such as the spatial and spectral distributions of accelerated electrons or characteristics of the solar atmosphere (e.g. density). Aims. We propose a new ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Most of our footpoint sizes and areas are upper limits where the measurements of the minor axes are upper limits. However, these upper limits are not likely to have been significantly increased by the albedo since Battaglia et al (2011) have shown that albedo increases the FWHM of a footpoint by less than 30%. The presence of extended albedo sources can in principle be inferred in the presence of compact footpoint sources from the relative intensities of the modulation amplitudes given by the finer and coarser subcollimators .…”
Section: Nonthermal Source Areasmentioning
confidence: 97%
“…Most of our footpoint sizes and areas are upper limits where the measurements of the minor axes are upper limits. However, these upper limits are not likely to have been significantly increased by the albedo since Battaglia et al (2011) have shown that albedo increases the FWHM of a footpoint by less than 30%. The presence of extended albedo sources can in principle be inferred in the presence of compact footpoint sources from the relative intensities of the modulation amplitudes given by the finer and coarser subcollimators .…”
Section: Nonthermal Source Areasmentioning
confidence: 97%
“…The affect of albedo may also have contributed to the estimated footpoint area. Battaglia et al (2011) estimated that albedo could result in increased source areas by up to 30% for energies between 10 and 100 keV. Given these considerations, the measured footpoint area from HXR imaging should be considered as an overestimate.…”
Section: X-ray Imagingmentioning
confidence: 99%
“…Since all C class flares were imaged at 25−50 keV, their footpoints could appear larger than they are as compared to the stronger flares. However, the albedo component has a much lower flux density than the footpoints and is therefore unlikely to influence the FWHM measurements significantly (see also Battaglia et al 2011).…”
Section: Scaling Of Geometric Parameters With Flare Importancementioning
confidence: 99%